Application Development of Cylindrical Roller Bearing for High-speed EMUs - LI Guodong; ZHAO Wenxue; HAN Qingli (机车电传动)
Aiming at the problems of tapered roller bearings applied in high-speed EMUs in our country, such as bearing grease leakage, abnormal temperature rise, and stripping, using forward design concept, combined the technical characteristics of cylindrical roller bearings of radial load capacity, high speed limit, strong maintaining lubrication capacity, the cylindrical roller bearings were developed for high-speed EMUs operation. Through the bench test, line test and batch applications, the proposed cylindrical roller bearings were validated to meet the application requirements of high-speed EMUs.